Correlating the triglyceride glucose index with short-term neurological and functional prognosis following intravenous thrombolysis in acute ischemic stroke patients - Hua, Defeng; Guo, Zhen (Frontiers in Neurology, 2025)
ObjectiveTo assess the correlation between the triglyceride glucose (TyG) index and short-term neurological and functional outcomes in patients with acute ischemic stroke (AIS) post-intravenous thrombolysis (IVT).MethodsThis prospective observational study included AIS patients treated with IVT within 4.5 h from symptom onset. The TyG index was calculated using fasting triglyceride and glucose levels. Neurological improvement was evaluated by a reduction in National Institutes of Health Stroke Scale (NIHSS) scores, and functional outcome by modified Rankin Scale (mRS) at discharge. Statistical analysis included correlation and regression analyses.ResultsAmong 150 AIS patients, the TyG index significantly correlated with both NIHSS (rho = 0.45, p < 0.01) and mRS (rho = 0.38, p < 0.01) scores at discharge. A higher TyG index was associated with neurological non-improvement (OR = 2.11, p = 0.002) and poor functional outcomes (OR = 1.89, p = 0.005) after adjustment for confounders.ConclusionThe TyG index is significantly associated with short-term outcomes in AIS patients post-IVT, suggesting its potential as a prognostic marker for stroke severity and recovery. Future studies with larger cohorts are needed to confirm these findings.